Comparative analysis of media discourse and the influence of social and political context in Serbian press 1904 and 1929 - Stančić, Kristina; Aleksić, Miloš (Politeia, 2017)
This paper provides a critical, comparative analysis of the newspaper articles of the daily Politika, from 1904 and 1929, with the emphasis on the importance of political, historical and social factors in their interpretation. Also, this paper stress the importance of the context, especially in the analysis of media discourse from a certain time difference, identifies the elements that form part of it and reveals that the interpretation of the text can be significantly modified by insight into its context. Also, the significance of the interdisciplinary paradigm in the research, i.e. the interaction of several different disciplines in dealing with these and similar topics, is also underlined.